MYO5B and bile salt export pump contribute to cholestatic liver disorder in microvillous inclusion disease. Issue 1 (27th May 2014) - Girard, Muriel; Lacaille, Florence; Verkarre, Virginie; Mategot, Raphael; Feldmann, Gerard; Grodet, Alain; Sauvat, Frédérique; Irtan, Sabine; Davit‐Spraul, Anne; Jacquemin, Emmanuel; Ruemmele, Frank; Rainteau, Dominique; et al.
<x xml:space="preserve">Abstract</x> Microvillous inclusion disease (MVID) is a congenital disorder of the enterocyte related to mutations in the MYO5B gene, leading to intractable diarrhea often necessitating intestinal transplantation (ITx). Among our cohort of 28 MVID patients, 8 developed a cholestatic liver disease akin to progressive familial intrahepatic cholestasis (PFIC). Our aim was to investigate the mechanisms by which MYO5B mutations affect hepatic biliary function and lead to cholestasis in MVID patients. Clinical and biological features and outcome were reviewed. Pretransplant liver biopsies were analyzed by immunostaining and electron microscopy. Cholestasis occurred before (n = 5) or after (n = 3) ITx and was characterized by intermittent jaundice, intractable pruritus, increased serum bile acid (BA) levels, and normal gamma‐glutamyl transpeptidase activity. Liver histology showed canalicular cholestasis, mild‐to‐moderate fibrosis, and ultrastructural abnormalities of bile canaliculi. Portal fibrosis progressed in 5 patients. No mutation in ABCB11/BSEP or ATP8B1/FIC1 genes were identified. Immunohistochemical studies demonstrated abnormal cytoplasmic distribution of MYO5B, RAB11A, and BSEP in hepatocytes. Interruption of enterohepatic BA cycling after partial external biliary diversion or graft removal proved the most effective to ensure long‐term remission. Conclusion: MVID patients are at risk of developing a PFIC‐like liver disease that may hamper outcome after ITx. Our results suggest that cholestasis in MVID patients results from (1) impairment of the MYO5B/RAB11A apical recycling endosome pathway in hepatocytes, (2) altered targeting of BSEP to the canalicular membrane, and (3) increased ileal BA absorption. Because cholestasis worsens after ITx, indication of a combined liver ITx should be discussed in MVID patients with severe cholestasis. Future studies will need to address more specifically the effect of MYO5B dysfunction in BA homeostasis. (Hepatology 2014;60:301–310)